Carrier material for local release of particulate matter
By using a non-gelling polymer carrier material formed by reversible bonding of multiple hydrophilic polymer units, the problem of local release of AAV on the surface of skin ulcers in the existing technology is solved, and efficient gene introduction specificity and Low off-target effects.
Patent Information
- Application Number
- CN202380045293.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-10-21
- Filing Date
- 2023-10-18
- Publication Date
- 2025-01-17
AI Technical Summary
The prior art is difficult to locally release adeno-associated virus (AAV) and other particulate matter on the surface of skin ulcers, resulting in insufficient specificity of gene introduction and a large off-target effect.
A non-gelling polymer formed by the reversible bonding of multiple hydrophilic polymer units is used as a carrier material, through which particulate matter such as AAV is released locally, increasing the specificity of gene introduction and reducing off-target effects.
It achieves the local release of AAV in affected parts such as the surface of skin ulcers, improves the specificity of gene introduction, reduces gene expression in distant parts such as the liver, and reduces the risk of toxicity.
Smart Images

Figure CN119325391A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to associative carrier materials for the local delivery of particulate matter, and in particular to carrier materials suitable for the local delivery of adeno-associated viruses (AAV). Background Art
[0002] Adeno-associated virus (AAV) is one of the most powerful vectors for in vivo gene delivery. Starting with clinically proven systemic replacement therapy for lipoprotein lipase deficiency, spinal muscular atrophy, retinal dystrophy, hemophilia, etc., its application in more localized pathological conditions has recently expanded significantly.
[0003] As the manufacturing methods of AAV vectors improve, the average dose of AAV vectors used clinically is increasing. Although high doses can be used to achieve more powerful phenotypes, most AAV vectors reach the liver and may cause toxicity in the liver or elsewhere. In this context, controlling the specificity of gene expression, that is, minimizing off-target effects, has become one of the important development directions. So far, attempts have been made to minimize off-target effects by selecting and manipulating the tissue / cell affinity of the AAV capsid, using tissue-specific promoters, and selecting routes of administration.
[0004] Non-healing wounds caused by bedsores, diabetic ulcers, and peripheral vascular insufficiency are of great importance in the age of aging society, and AAV-based in vivo gene delivery is expected to become one of the most powerful treatments. In particular, in recent years, the discovery that wound-resident mesenchymal cells can be reprogrammed into epithelial cells in vivo using AAV may lead to the development of innovative treatments, such as re-epithelialization from ulcer surfaces. Prior art literature Non-patent literature
[0005] Non-patent literature 1: Kurita, M., Izpisua BelmOnte, JC, Suzuki, K., Okazaki, M., JD DermOl Sci 2019;95:8-12. Non-patent literature 2: Kurita, M., AraOka, T., Hishida, T., et al., Nature 2018; 561: 243-247. Summary of the invention Problems to be solved by the present invention
[0006] Therefore, an object of the present invention is to provide a biocompatible carrier material capable of releasing particulate matter such as adeno-associated virus onto the surface of skin ulcers. Means used to solve problems
[0007] In order to solve the above-mentioned problems, the present inventors conducted intensive research and found that by using a non-gelling polymer composed of a plurality of hydrophilic polymer units reversibly bonded together as a carrier material, particulate matter can be locally released to the affected area such as the surface of an ulcer, thereby increasing the specificity of gene introduction and reducing off-target effects, thereby completing the present invention.
[0008] That is, in one aspect, the present invention provides: <1> A carrier material for topical release of a particulate substance, the carrier material having a finite zero shear viscosity greater than 500 Pa·s, comprising a non-gelling polymer composed of a plurality of hydrophilic polymer units reversibly bonded together, and containing a solvent, the polymer units comprising a first branched polymer unit having a total of two or more boronic acid-containing groups at a side chain or a terminal and a second branched polymer unit having a total of two or more diol groups at a side chain or a terminal, wherein a polymer concentration (c) in the carrier material is greater than or equal to an overlap concentration (c*) of the polymer units; <2> According to the carrier material described in <1> above, the particulate matter has a diameter in the range of 10-100 nm; <3> According to the carrier material described in <1> above, the particulate matter is adeno-associated virus (AAV); <4> The carrier material according to <1> above, wherein the polymer unit has a polyethylene glycol skeleton or a polyethylene skeleton; <5> According to the carrier material described in <1> above, the first branched polymer unit is a bi-branched, tri-branched, or tetra-branched polyethylene glycol; <6> According to the carrier material described in <1> above, the second branched polymer unit is a dibranched, tribranched or tetrabranched polyethylene glycol, or a dibranched polyvinyl alcohol; <7> According to the carrier material described in <1> above, the first branched polymer unit has 5×10 3 -1×10 5 The molecular weight (M w ); <8> According to the support material described in <1> above, the boronic acid group is an aryl boronic acid that can be substituted by a halogen atom; <9> The carrier material according to <1> above, wherein the diol group has an open-ring structure of a sugar derivative; <10> The carrier material according to <1> above, further comprising a third polymer unit having a total of two or more boronic acid groups or diol groups at the side chain or the end; <11> The carrier material according to <1> above, characterized in that the osmotic pressure of the carrier material is less than the osmotic pressure Π represented by the following formula: 0 (Pa): Mathematical formula 1: In the formula, c represents the polymer concentration (g / L), c* represents the overlap concentration of the polymer unit, R represents the gas constant, T represents the absolute temperature, and M is the weight average molecular weight of the polymer unit; <12> According to the carrier material described in <1> above, the carrier material has the ability to release the particulate substance in vivo as the carrier material dissolves, and the dissolution rate L and the release rate M at this time satisfy the following relationship: Mathematical formula 2: L=A×M In the formula, A is in the range of 0.9<A<1.1; <13> According to the carrier material described in <1> above, the use of the local release is gene therapy for skin ulcers.
[0009] In another aspect, the present invention provides: <14> A composition comprising the carrier material described in any one of <1> to <13> above and the granular substance stored therein; <15> A method of treatment, comprising applying the composition described in <14> above to an affected area; <16> A kit for forming a carrier material according to any one of <1> to <13>, comprising at least a composition A containing a first branched polymer unit having two or more boronic acid groups at a side chain or a terminal and a composition B containing a second branched polymer unit having two or more diol groups at a side chain or a terminal, wherein the carrier material has a finite zero shear viscosity greater than 500 Pa·s, and a polymer content (c) in the carrier material is greater than or equal to an overlap concentration (c*) of the polymer units; <17> The kit according to <16>, further comprising a polymer solution C containing a third polymer unit having a total of two or more boronic acid-containing groups or diol groups at a side chain or a terminal. Effects of the Invention
[0010] According to the present invention, a biocompatible carrier material capable of locally releasing adeno-associated virus and other granular substances on the surface of skin ulcers can be provided, thereby enabling safer application in gene therapy for skin ulcers and the like. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] Figure 1 Schematic diagram showing the structure of the carrier material (PEG mucus) of the present invention used in the examples. Figure 2 Schematic diagram showing the structure of the carrier material (PEG hydrogel and PEG sponge) of the comparative example used in the examples. Figure 3 are images showing the viscosity of each carrier material used in the examples. Figure 4 Graph showing the change in Young's modulus of each carrier material used in Examples over time. Figure 5 Confocal microscope images showing the internal network structure of each support material used in the examples. Figure 6 The figure shows the dissolution rate and release rate obtained for each carrier material used in the examples. The solid circle represents the release rate (left axis), and the hollow circle represents the dissolution rate (right axis). Figure 7 For drawing Figure 6 A plot of the release rate versus dissolution rate obtained in . Figure 8 Schematic diagram showing the experimental sequence for introducing AAV genes into skin ulcers. Fig. 9 These are fluorescence microscope images of the ulcer surface when AAV gene introduction was performed using various vector materials. Fig.10 The graph shows the number of GFP-positive cells expressed on the surface and in the deep layer when AAV gene transfer was performed using each vector material. Fig.11 Stereoscopic and fluorescent microscopic images of the ulcer surface when surface-specific AAV gene introduction was performed using PEG mucus and PBS. Fig.12 This is a graph showing the number of GFP-positive cells expressing on the surface and in the deep layer when surface-specific AAV gene transfer was performed using each vector material. Fig.13 Fluorescence microscopy images of liver tissue when AAV gene introduction was performed using PEG mucus and PBS. Fig.14 is a graph showing AAV titers in the liver. Fig.15 Schematic representation of the experimental sequence used to evaluate the dispersion behavior of nanoparticles in the surface of skin ulcers. Fig.16 It is a graph showing the number of particles on the surface when surface-specific AAV gene introduction was performed using each carrier material. Fig.17 Schematic diagram of the local infection mechanism using PEG carriers (a in the upper figure is PEG hydrogel and PEG sponge, and b in the lower figure is PEG mucus). DETAILED DESCRIPTION
[0012] The following describes embodiments of the present invention. The scope of the present invention is not limited to the above description, and other than the following examples, the present invention can be implemented with appropriate changes without departing from the gist of the present invention.
[0013] 1. Carrier material of the present invention The carrier material of the present invention is a carrier material for locally releasing particulate substances, characterized in that the carrier material has a finite zero shear viscosity greater than 500 Pa·s, comprises a non-gelled polymer formed by reversibly bonding multiple hydrophilic polymer units, and contains a solvent, the polymer units include a first branched polymer unit having a total of more than two boronic acid groups on the side chain or the end and a second branched polymer unit having a total of more than two diol groups on the side chain or the end, and the polymer concentration (c) in the carrier material is greater than or equal to the overlapping concentration (c*) of the polymer units. Hereinafter, the polymer units constituting the support material of the present invention and the characteristics of the support material will be described in more detail.
[0014] (1-1) Polymer unit The polymer units constituting the carrier material of the present invention can be connected to each other to form a non-gel carrier material, more specifically, the following branched polymer: in the final carrier material, the polymer units are connected by reversible bonding of equilibrium reaction to form a network structure, especially an aggregate of a three-dimensional network structure. Such polymer units are preferably hydrophilic polymers. The hydrophilic polymer can use a polymer with affinity for water known in the art, but is preferably a biocompatible polymer with a polyalkylene glycol backbone or a polyethylene backbone.
[0015] The polymer with polyalkylene glycol backbone preferably includes the polymer species of the branch with multiple polyethylene glycol backbones, and the polyethylene glycol of dibranching, tribranching or tetrabranching is particularly preferred.The carrier material composed of tetrabranched polyethylene glycol backbone is generally referred to as Tetra-PEG carrier material, and the known mesh structure network is constructed by the AB type cross-terminal coupling reaction between tetrabranched polymers, and the tetrabranched polymers each have two or more functional groups (Matsunaga et al., MacromOlecules, VOl.42, NO.4, pp.1344-1351, 2009) that can react with each other at the end. In addition, Tetra-PEG carrier material can be easily manufactured on site by simply mixing two liquids of each polymer solution, and the carrier materialization time can also be controlled by adjusting pH or ionic strength during carrier material preparation. It is known that the carrier material (Fujiyabu et al., Science Advances, Vol.8, eabk0010, 2022) with excellent physical properties can also be manufactured by tribranched polyethylene glycol. Furthermore, since these carrier materials contain PEGz as a main component, they also have excellent biocompatibility.
[0016] Examples of the hydrophilic polymer having a polyethylene skeleton include polyalkyl methacrylates such as polymethyl methacrylate, polyacrylates, polyvinyl alcohol, poly-N-alkyl acrylamide, polyacrylamide, etc. The hydrophilic polymer having a polyethylene skeleton is preferably dibranched, and for example, dibranched polyvinyl alcohol is suitable.
[0017] The hydrophilic polymer has a 5×10 3 -1×10 5 range, preferably 5×10 3 -5×10 4 , more preferably 1×10 4 -5×10 4 The weight average molecular weight (M w ).
[0018] The hydrophilic polymer used in the present invention is a combination of a first branched polymer unit having two or more boronic acid groups in a side chain or at a terminal and a second branched polymer unit having two or more diol groups in a side chain or at a terminal. Wherein, the total number of boronic acid groups and diol groups is preferably 5 or more. It is further preferred that these functional groups are present at the terminal. For example, when the first polymer unit has a dibranched, tribranched, or tetrabranched structure, it is preferred that the boronic acid groups are present at the respective branched ends, and, when the second polymer unit has a dibranched, tribranched, or tetrabranched structure, it is preferred that the diol groups are present at the respective branched ends.
[0019] When the polymer unit has such a boronic acid group and a diol group, as shown in the following equilibrium reaction formula, by chemically reacting the boronic acid site and the OH group of the polyol, the carrier material of the present invention having a structure in which the polymer units are reversibly bonded to each other can be obtained. Further, the specific structures of the boronic acid group and the diol group shown in the reaction formula are only examples and are not limited to these, and as described below, the boronic acid group and the diol group other than these types may be used. Chemical formula 1
[0020] The boronic acid-containing group present in the first polymer unit is not particularly limited as long as it has a boronic acid structure, but for example, it may be an aryl boronic acid, preferably an aryl boronic acid that can be substituted by a halogen atom. As the aryl boronic acid, phenyl boronic acid is preferred. The boronic acid-containing groups may be the same or different, but are preferably the same. By having the same functional group, the reactivity with the diol group becomes uniform, making it easier to obtain a support material with a uniform structure.
[0021] There is no particular limitation on the diol group present in the second polymer unit, as long as it is a functional group having two or more hydroxyl groups (OH groups), but it can be a sugar alcohol having a structure derived from sugar, preferably an open-loop structure having a sugar derivative. Such sugar can be any of a monosaccharide, a disaccharide, or a polysaccharide, typically, a monosaccharide such as glucose or fructose. In addition, it can be an aromatic polyol group, an aliphatic polyol group, or a diol group in which more than one carbon in the molecule is substituted by a heteroatom. The diol groups can be the same or different, but are preferably the same. By having the same functional group, the reactivity with the boric acid group becomes uniform, making it easier to obtain a carrier material with a uniform structure.
[0022] Preferably, the first branched polymer unit has 5×10 3 -1×10 5 The weight average molecular weight (M w ). Similarly, the second branched polymer unit has 5×10 3 -1×10 5 The molecular weight (M w ).
[0023] Preferred non-limiting specific examples of the first polymer unit include, for example, a compound represented by the following formula (I) having four branches of a polyethylene glycol backbone and having a boronic acid-containing group at each end. Chemical formula 1
[0024] In formula (I), X is a boronic acid group. In a preferred embodiment, X may be fluorophenylboronic acid having the following structure (in some structures, the wavy line portion is R 11 -R 14 The connection part. ). Chemical formula 1
[0025] In formula (I), n 11 -n 14 Can be the same or different. 11 -n 14 The closer the values of are, the more uniform the three-dimensional structure is and the higher the strength is. Therefore, in order to obtain a high-strength carrier material, it is preferred that they are the same. 11 -n 14 If the value of is too high, the strength of the carrier material will be weakened. 11 -n 14 If the value of is too low, it will be difficult to form a support material due to the steric hindrance of the compound. 11 -n 14 It has an integer value of 20-570, preferably 20-290, more preferably 50-290.
[0026] In the above formula (I), each is the same or different, R 11 -R 14 It is the connection site between the functional group and the core part. 11 -R 14 They may be the same or different, but are preferably the same to produce a high-strength support material with a uniform three-dimensional structure. 11 -R 14 Indicates direct bonding, C 1 -C 7 Alkylene, C 2 -C 7 Alkenylene, -NH-R 15 -、-CO-R 15 -、-R 16 -OR 17 -、-R 16 -NH-R 17 -、-R 16 -CO2-R 17 -、-R 16 -CO 2 -NH-R 17 -、-R 16 -CO-R 17 -, or -R 16 -CO-NH-R 17 -. Among them, R 15 Represents C 1 -C7 Alkylene. 16 Represents C 1 -C 3 Alkylene. 17 Represents C 1 -C 5 Alkylene.
[0027] Among them, "C 1 -C 7 "Alkylene" refers to an alkylene group having 1 or more and 7 or less carbon atoms and may have a branched chain, and refers to an alkylene group having a straight chain C 1 -C 7 Alkylene or one or more branched C 2 -C 7 Alkylene (including branched carbon number of 2 or more and 7 or less). 1 -C 7 Examples of the alkylene group are methylene, ethylene, propylene and butylene. 1 -C 7 Examples of alkylene groups include -CH 2 -、-(CH 2 ) 2 -、-(CH 2 ) 3 -、-CH(CH 3 )-、-(CH 2 ) 3 -、-(CH(CH 3 )) 2 -、-(CH 2 ) 2 -CH(CH 3 )-、-(CH 2 ) 3 -CH(CH 3 )-、-(CH 2 ) 2 -CH(C 2 H 5 )-、-(CH 2 ) 6 -、-(CH 2 ) 2 -C(C 2 H 5 ) 2 - and - (CH 2 ) 3 C(CH 3 ) 2 CH 2 -wait.
[0028] ”C 2 -C 7The term "alkenylene" refers to a main chain or branched alkenylene group having 2 to 7 carbon atoms and having one or more double bonds in the chain, and includes, for example, a divalent group having a double bond formed by removing 2 to 5 hydrogen atoms of adjacent carbon atoms from the alkylene group.
[0029] On the other hand, preferred non-limiting specific examples of the second polymer unit include a compound represented by the following formula (II), which has four polyethylene glycol backbone branches and has a diol group at each end. Chemical formula 3
[0030] In formula (I), Y is a diol group. In a preferred embodiment, Y may be a polyol having an open-ring structure of a glucose derivative having the following structure (in the partial structure, the wavy line portion is R 21 -R 24 The connection part. ). Chemical formula 4
[0031] In the above formula (II), n 21 -n 24 Can be the same or different. 21 -n 24 The closer the values are, the more uniform the three-dimensional structure of the carrier material is, and the higher the strength is, preferably the same. 21 -n 24 If the value of is too high, the strength of the carrier material will be weaker. 21 -n 24 If the value of is too low, it will be difficult to form a support material due to the steric hindrance of the compound. 21 -n 24 The integer value includes 20-570, preferably 20-290, and more preferably 50-290.
[0032] In the above formula (II), R 21 -R 24 It is the connection site between the functional group and the core part. 21 -R 24 They may be the same or different, but are preferably the same to produce a high-strength support material with a uniform three-dimensional structure. 21 -R 24 The same or different, indicating direct combination, C 1 -C 7 Alkylene, C 2 -C 7 Alkenylene, -NH-R 25 -、-CO-R 25 -、-R26 -OR 27 -、-R 26 -NH-R 27 -、-R 26 -CO2-R 27 -、-R 26 -CO2-NH-R 17 -、-R 26 -CO-R 27 -, or -R 26 -CO-NH-R 27 -. Among them, R 25 Represents C 1 -C 7 Alkylene. 26 Represents C 1 -C 3 Alkylene. 27 Represents C 1 -C 5 Alkylene.
[0033] In this specification, alkylene and alkenylene may have one or more arbitrary substituents. Such substituents include, but are not limited to, alkoxy, halogen atoms (which may be any fluorine atom, chlorine atom, bromine atom, or iodine atom), amino, mono- or di-substituted amino, substituted silyl, acyl, or aryl. When an alkyl group has two or more substituents, they may be the same or different. The same applies to the alkyl part of other substituents (such as alkoxy or aralkyl, etc.) containing the alkyl part.
[0034] Furthermore, in this specification, when a functional group is defined as "may have a substituent", the type, substitution position and number of the substituent are not particularly limited, and when there are two or more substituents, they may be the same or different. The substituent may include, but is not limited to, for example, an alkyl group, an alkoxy group, a hydroxyl group, a carboxyl group, a halogen atom, a sulfo group, an amino group, an alkoxycarbonyl group, an oxo group, etc. These substituents may have other substituents.
[0035] In addition, in the present invention, in addition to the first and second polymer units, a third polymer unit having two or more boronic acid groups or diol groups in the side chain or at the end may be used. The third polymer unit is preferably a hydrophilic polymer, and its structure is similar to the above description about the first and second polymer units.
[0036] (1-2) Physical properties of carrier materials, etc. As described above, the carrier material of the present invention has a network structure formed by the first branched polymer unit and the second branched polymer unit, but as a characteristic of the formed carrier material itself, as described above, its polymer concentration (polymer content) (c) is characterized by being equal to or higher than the overlap concentration (c*) of the polymer units (c*≤c). Preferably, the polymer concentration (c) may be 1.5 times or more of c* (1.5c*≤c), more preferably 2 times or more of c* (2c*≤c).
[0037] In addition, the carrier material of the present invention is characterized in that the limited value of zero shear viscosity is 500Pa·s or more. Preferably, it can be 1000Pa·s or more, and more preferably, it can be 1200Pa·s or more. "Zero shear viscosity" refers to the viscosity when the shear rate is greater than 0. The calculation method of zero shear viscosity can be calculated by a known method. For example, as described in Polymer Physics (POlymer Physics) (M. Rubinstein, R. COlby), the slope of the angular frequency of the loss modulus in the low frequency region can be measured by dynamic viscoelasticity. Thus, physical properties such as viscosity can be maintained while reducing the osmotic pressure of the desired polymer solution to the desired range.
[0038] Here, the "overlap concentration" (also called "overlap concentration") refers to the concentration at which polymers in a solvent begin to spatially contact each other. Generally, the overlap concentration c* is represented by the following formula. Mathematical formula 3 c*=3M w / (4π·α·N A ·R g 3 ) (In the formula, M w is the weight average molecular weight of the polymer, α is the specific gravity of the solvent, N A is Avogadro's constant, R g is the radius of inertia of the polymer. ).
[0039] The calculation method of the overlap concentration c* can refer to, for example, Polymer Physics (by M. Rubinstein and R. Colby). Specifically, for example, it can be calculated by measuring the viscosity of a dilute solution using the Flory-FOx formula.
[0040] The carrier material of the present invention contains a solvent and has a polymer concentration (polymer content) of 80 g / L or less, preferably 60 g / L or less, and more preferably 40 g / L or less. The lower limit of the polymer concentration is not particularly limited, but from the viewpoint of obtaining the desired viscosity and other physical properties, the lower limit is preferably 10 g / L or more. This numerical range is the effective polymer concentration of the carrier material of the present invention to reduce the osmotic pressure of the polymer solution by pouring into the associative site. The solvent in the carrier material is preferably water, or a mixed solvent of water and an organic solvent.
[0041] In addition, the osmotic pressure of the carrier material of the present invention is preferably in the range of 100-20000 Pa, more preferably in the range of 10-8500 Pa. As mentioned above, although the carrier material of the present invention is a polymer aqueous solution, it achieves a lower osmotic pressure than a polymer solution having a main chain of the same composition. Wherein, the osmotic pressure is represented by the following formula: Mathematical formula 4 Π=1.71c 2.31 (In the formula, Π represents the osmotic pressure (Pa), and c represents the polymer content in the carrier material (g / L).).
[0042] Moreover, the osmotic pressure II of the carrier material of the present invention is preferably less than the osmotic pressure II represented by the formula 0 (Pa)(Π<Π 0 ). Osmotic pressure 0 This is the theoretical value of the osmotic pressure when it is the above-mentioned "polymer having a main chain of the same composition". Mathematical formula 5 (In the formula, c represents the polymer concentration (g / L), c* represents the overlap concentration of the polymer unit, R represents the gas constant, T represents the absolute temperature, and M is the weight average molecular weight of the polymer unit)
[0043] The solvent contained in the carrier material of the present invention can use any solvent as long as it dissolves the aggregates formed by the above-mentioned polymer units, but typically, water or an organic solvent can be used. As the organic solvent, alcohols such as ethanol, polar solvents such as DMSO can be used. Preferably, the solvent is water.
[0044] The carrier material of the present invention can typically be manufactured by mixing a raw material containing a first polymer unit with a raw material containing a second polymer unit. When a solution containing a polymer unit is used as a raw material, the concentration, addition rate, mixing rate, and mixing ratio of each solution are not particularly limited and can be appropriately adjusted by a person skilled in the art. As the solvent of such a solution, as described above, alcohols such as water, ethanol, DMSO, etc. can be used. When the solution is an aqueous solution, a suitable pH buffer such as a phosphate buffer can be used. Preferably, the carrier material of the present invention can be prepared using the following kit.
[0045] The particulate matter released locally by the carrier material of the present invention is not particularly limited as long as it is a substance that can be retained in the carrier material, but preferably has a diameter in the range of 10-100 nm. A typical example of such a particulate matter is adeno-associated virus (AAV). As described above, according to the carrier material of the present invention, AAV can be locally released to the affected part, such as the surface of an ulcer, etc., thereby increasing the specificity of gene introduction and reducing off-target effects.
[0046] The mechanism of such local release is that the above-mentioned granular substance can be released in vivo when the carrier material of the present invention is dissolved. Preferably, the dissolution rate L (dissolution rate) and the release rate M (release rate) at this time satisfy the following relationship: L=A×M (In the formula, A is in the range of 0.9<A<1.1).
[0047] (1-3) Kit In another aspect, the present invention relates to a kit for forming the above-mentioned carrier material.
[0048] Such a kit comprises at least a composition A comprising a first branched polymer unit having two or more boronic acid groups in a side chain or at a terminal and a composition B comprising a second branched polymer unit having two or more diol groups in a side chain or at a terminal. By mixing them, the carrier material of the present invention having a network structure composed of a plurality of polymer units can be obtained in situ. The types of the first and second polymer units are as described above.
[0049] Compositions A and B containing polymer units may be in a solution state or a powdered form, but are preferably in a solution state. Depending on the circumstances, one of compositions A and B may be a solution, and the other may be in a powdered form. Wherein, for convenience, compositions A and B in a solution state are referred to as polymer solutions A and B, respectively. The solvent in polymer solutions A and B is water, but depending on the circumstances, a mixed solvent containing alcohols such as ethanol or other organic solvents may also be used. Preferably, polymer solutions A and B are aqueous solutions containing water as a single solvent. The capacity of polymer solutions A and B may be appropriately adjusted according to the area of the affected part etc. and the complexity of the structure thereof, but are usually in the range of 0.1-20 ml each, preferably 1-10 ml.
[0050] The pH of polymer solutions A and B is usually in the range of 4 to 10, preferably 5 to 8, and more preferably 7 to 8. The pH of polymer solutions A and B can be adjusted using a pH buffer known in the art. For example, the pH can be adjusted to the above range by using a citric acid-phosphate buffer (CPB) and changing the mixing ratio of citric acid and disodium hydrogen phosphate.
[0051] As a means of mixing polymer solutions A and B, for example, two liquid mixing syringes disclosed in International Publication No. WO2007 / 083522 can be used. There is no particular restriction on the temperature of the two liquids when mixing, as long as the temperature is sufficient to dissolve each polymer unit and each liquid has a fluid state. For example, the temperature of the two liquids can be different, but since the two liquids are easier to mix, it is preferred that the temperature of the two liquids is the same.
[0052] The kit of the present invention may further include a polymer solution C comprising a third polymer unit having a total of two or more boronic acid-containing groups or diol groups at a side chain or a terminal.
[0053] The kit of the present invention may include a container for storing compositions A and B. For example, when compositions A and B are in a solution state, a device such as a sprayer storing solutions A and B may be used. The sprayer may appropriately use any sprayer known in the art, preferably a medical sprayer. In this case, as one aspect of the present invention, it may be a medical device storing compositions A and B, preferably a sprayer. Example
[0054] Hereinafter, the present invention will be described in more detail with reference to Examples, but the present invention is not limited thereto.
[0055] 1 . Preparation of carrier materials As polymer units constituting the carrier material, Tetra-PEG-GDL having a diol group (an open ring structure of gluconolactone) at the terminal of tetra-branched tetraethylene glycol and Tetra-PEG-FPBA having a fluorophenylboronic acid group at the terminal were synthesized.
[0056] The following raw materials were used. Tetra-PEG-NH 2 (Molecular weight M w 5k, 10k, and 20k respectively; Yuka Sangyo Co., Ltd.); 4-carboxy-3-fluorophenylboronic acid (FPBA) (Fujifilm Wako Pure Chemical Industries, Ltd.); 4-(4,6-dimethoxy-1,3,5-triazin-2-yl)-4-methylmorpholinium chloride (DMT-MM) (Fujifilm Wako Pure Chemical Industries, Ltd.); glucono-δ-lactone (GDL) (Tokyo Chemical Industry Co., Ltd.).
[0057] Synthesis of Tetra-PEG-GDL Tetra-PEG-NH 2 Dissolved in methanol at a concentration of 50 mg / mL, and added to Tetra-PEG-NH 2 Add 10 times the molar ratio of gluconolactone and 20 times the molar ratio of triethylamine to the terminal amino group of the reaction mixture, and stir at 35°C for 3 days. Transfer the reaction mixture to a dialysis membrane (MWCO: 6-8,000 at 20k; MWCO: 3,500 at 10k and 5k), dialyze with methanol for 2 days, dialyze with water for 2 days, pass through a 0.45um syringe filter, and then freeze-dry and recover in powder form. 1 H-NMR confirmed the completion of the synthesis.
[0058] Synthesis of Tetra-PEG-FPBA Tetra-PEG-NH 2 Dissolved in methanol at a concentration of 50 mg / mL, and added to Tetra-PEG-NH 2Add 5 times the molar ratio of FPBA and 10 times the molar ratio of DMT-MM to the terminal amino group and stir at room temperature overnight. Transfer the reaction solution to a dialysis membrane (MWCO: 6-8,000 when 20k; MWCO: 3,500 when 10k and 5k), dialyze with an aqueous hydrochloric acid solution (10mM) for half a day, dialyze with an aqueous sodium hydroxide solution (10mM) for half a day, dialyze with a phosphate buffer solution (pH7.4, 10mM) for half a day, dialyze with saline (100mM) for 1 day, and finally dialyze with pure water for 1 day. After passing through a 0.45um syringe filter, lyophilize and recover in the form of powder. 1 H-NMR confirmed the completion of the synthesis.
[0059] Using double-branched PEG and triple-branched PEG as starting materials, various polymer units with GDL termini and FPBA were similarly adjusted.
[0060] Synthesis of support materials Solutions containing the obtained polymer units were prepared under the following conditions, and these polymer solutions were mixed to synthesize a support material. Polymer solution A Concentration: 2-10wt% Tetra-PEG-GDL pH: 7.4 Polymer solution B Concentration: 2-10wt% Tetra-PEG-FPBA pH: 7.4
[0061] 2 . Assessment of osmotic pressure The osmotic pressure of the carrier material obtained above was measured. The results when the molecular weight of the monomer unit was 10k and 40k are shown in Figure 1 and Figure 2 , as the polymer content c increases, the osmotic pressure Π increases. Figure 1 The solid line in the graph shows the regression curve of these data. Regardless of pH, number of branches, or molecular weight, all data follow the same curve. This regression curve is represented by the following mathematical formula. Mathematical formula 6 ∏=1.71c 2.31 (In the formula, Π represents the osmotic pressure (Pa), and c represents the polymer content in the carrier material (g / L).)
[0062] As a comparative example, Figure 1 and Figure 2The osmotic pressure results of common polymer solutions without associative functional groups (double-branched, three-branched, and four-branched PEG aqueous solutions with carboxyl groups at the ends) are also shown. In this case, the osmotic pressure increases with increasing concentration, but it shows a concentration dependence different from that of the carrier material of the present invention, that is, there is almost no dependence on the number of branches, and the osmotic pressure decreases with increasing molecular weight. It is known that the osmotic pressure of a polymer solution is usually independent of the molecular weight of the polymer, the type of the main chain, and the solvent, and can be approximated by the following formula (*) as described above. Mathematical formula 7
[0063] Furthermore, regarding the overlap concentration c*, the values of c*(10k)=59 g / L, c*(20k)=34 g / L, and c*(40k)=19 g / L were taken.
[0064] In order to standardize the effect of polymer shape, the vertical and horizontal axes are replaced by the following parameters: Figure 3 shown. Mathematical formula 8 Mathematical formula 9
[0065] It can be seen that the osmotic pressure of the polymer solution of the comparative example follows Figure 3 On the other hand, it can be seen that the carrier material of the present invention is consistent with the formula (*) in the region of c / c*>3, but at a concentration lower than this, the osmotic pressure becomes lower than the theoretical value of the formula (*), as described above, following the following formula. Mathematical formula 10 ∏=1.71c 2.31
[0066] And, according to the presence or absence of associative properties, the viscosity measurement results of the double-branched PEG (10k) are shown in the following table. The viscosity adopts the zero shear viscosity. It is found that the viscosity of the solution containing the carrier material of the present invention is compared with the viscosity of the polymer (without associative functional groups) made of the same polymer skeleton. The viscosity is not reduced by attaching associative functional groups, and it is not inferior to the existing polymer solution preparations. Table 1
[0067] 3. Design and Characterization of PEG Carriers: Comparison of Hydrogels, Sponges, and Mucus The polymer unit synthesized in 1. above is used to prepare the carrier material (i) of the present invention ( Figure 1 For comparison, PEG-derivatized carriers (ii) and (iii) with different cross-linking strategies and pore sizes were used. Figure 2 ). (i) PEG mucus: Tetra-PEG-GDL and Tetra-PEG-FPBA are mixed to form a reversibly cross-linked viscoelastic polymer liquid with cyclic ester bonds. Corresponding to the carrier material invented in this invention; (ii) PEG hydrogel; a synthetic hydrogel as an artificial extracellular matrix (ECM) cross-linked with Tetra-PEG-PA and Tetra-PEG-GS to form amide bonds and introduced ester bonds as hydrolyzable fragments of the hydrogel; (iii) PEG sponge: A porous hydrogel with a phase-separated structure introduced into the PEG hydrogel obtained by adding potassium sulfate to a polymer unit solution.
[0068] These PEG supports have different characteristics and structures. The differences in mechanical properties can be observed macroscopically during compression. The PEG hydrogel and PEG sponge are shown to be completely elastically deformed, while the PEG mucus gradually loses its original shape over time. Overall, when the PEG mucus prepared in a spherical shape is held with tweezers, it can maintain its shape like a solid. However, the grabbed mucus falls from the tweezers like a high viscosity liquid and eventually becomes flat on the table ( Figure 3 The differences between these supports were quantified by stress relaxation tests observing the time dependence of Young's modulus (E(t)) after a step strain was applied to the support. That is, E(t) decreased significantly over time only in the PEG mucus, falling below the measurement limit in about 10 seconds. On the other hand, although this value in the PEG sponge decreased slightly due to water extraction, the PEG sponge / PEG hydrogel showed certain limited values after 10 seconds ( Figure 4 ).
[0069] Next, the structural differences were evaluated by microscopic observation of PEG carriers prepared with red fluorescently labeled PEG precursors (the terminal portion of the PEG precursor was partially modified with a red fluorescent pigment). For the PEG sponge, an island structure with dispersed black cavities was observed in the image, with a pore size of the order of 10 μm, but for the PEG hydrogel and mucus, no characteristic structure was observed, indicating a network structure of the order of nm ( Figure 5 ). Phase separation is induced by adding inorganic salts, thereby reducing the solubility of PEG resulting in an opaque hydrogel. During the gelation process, PEG precursors bind to each other to increase the molecular weight and promote phase separation. The salt concentration is appropriately set to not induce phase separation of the original precursor solution but to induce phase separation during the gelation process.
[0070] In vitro evaluation of PEG support properties In order to investigate the differences in physical properties between PEG supports in detail, in vitro comparative analysis was further performed. The conditions of the experimental model facilitate easy understanding of dissolution kinetics. Red fluorescent-labeled PEG supports were prepared on culture inserts with a pore size of 8.0 μm (smaller materials can pass through). In particular, in order to evaluate the PEG mucus in detail, another PEG mucus designed to melt faster than ordinary PEG mucus was prepared (the molar ratio of double-branched to quadruple-branched polymers was set to 5:95, hereinafter referred to as "PEG soft mucus"). The dissolution rate calculated by measuring the fluorescence intensity of the dissolution samples passing through the insert at predetermined time intervals was gradually increased on each scaffold, and the 24-hour dissolution rate (D 样品 ) is D 水凝胶 =19%, D 海绵 =16%, D 粘液 =86%, D 软粘液 =90%( Figure 2 b). In addition, fluorescent nanoparticles with a diameter of 30 nm were encapsulated as a model material with a diameter similar to that of AAV, and the release curve of the fluorescent nanoparticles from the PEG carrier was calculated. The release behavior of the particles encapsulated in each carrier showed a trend similar to the dissolution behavior, and the release rate (R sample) for 24 hours was R hydrogel = 38%, D sponge = 33%, D mucus = 75%, and D soft mucus = 92%, and it was found that the dissolution of the carrier controlled the release of the nanoparticles ( Figure 6 ). When the dissolution rate is plotted against the release rate ( Figure 7 ), which are the same for PEG slime. This strong correlation indicates that particle release is mainly due to the dissolution of PEG slime. This result suggests that PEG slime is thermodynamically liquid, dissolving outside the membrane (in vivo) and transmitting particle diffusion.
[0071] In particular, the initial release rate was almost constant within 7 hours, i.e., reaching an ideal zero-order release rate. This result is considered to be based on the fact that the dissolution that controls the release of particles occurs only through the membrane and is therefore approximately zero-order. On the other hand, the particle release in the PEG hydrogel and sponge is not relevant in the high release rate region. This is because these carriers are solid and the particles are mainly released by diffusion.
[0072] Efficiency of AAV gene transfer in skin ulcers For the development of therapeutic drugs, gene delivery methods with high specificity for the ulcer surface are preferred. To examine the effect of PEG vectors on AAV-mediated gene delivery into skin ulcers, skin ulcers were created on the backs of mice using a skin chamber model equipped with a sterile silicone chamber. GFPNLS-AAVDJ (an AAV optimized for skin ulcer cells encoding GFP containing a nuclear localization signal (NLS)) was mixed with the PEG vector and inoculated into the ulcer ( Figure 8 Considering the expression time of AAV-based introduced genes and the cell turnover rate, a 72-hour interval was used as the experimental time range for the following quantitative analysis. Observation of the ulcer surface by fluorescence stereomicroscope showed that the frequency of GFPNLS-positive cells was higher in animals treated with AAV-encapsulated PEG mucus, PEG soft mucus, or PBS than in animals treated with PEG hydrogel and PEG sponge ( Fig. 9 and Fig.10 ).
[0073] Surface-specific AAV gene delivery in skin ulcers Encapsulation with PEG hydrogel and PEG sponge reduced the efficiency of gene delivery into the surface of skin ulcers, whereas PEG mucus encapsulation retained the original intensity observed with PBS. This suggests that the specificity of gene delivery in the surface layer of skin ulcers is emphasized, making PEG mucus more suitable for further histological evaluation. Ulcers treated with GFPNLS-AAVDJs, PEG mucus, PEG soft mucus, and PBS were prepared, and the frequency of GFPNLS-positive cells in the surface (granulation tissue and adipose tissue) and deep (fascia and muscle) layers was analyzed histologically. Consistent with the results of stereological evaluation, there were no significant differences in the surface layer between PEG mucus, PEG soft mucus, or PBS animals. In contrast, the number of GFPNLS-positive cells in the deep tissue was significantly reduced in animals treated with PEG mucus and soft mucus, and the reduction was more significant in animals treated with PEG mucus ( Fig.11 and Fig.12 ). Since the local layer-inherent efficiency of gene delivery was enhanced when PEG mucus carriers were used, the impact on distant off-target effects was further investigated.
[0074] Reduction of distant off-target gene expression in the liver As with most AAVs, the long-range off-target effects of the AAVDJ vector are concentrated in the liver. To investigate the effects of PEG mucus encapsulation, off-target GFPNLS expression in the liver was assessed 28 days after ulcer inoculation in the skin chamber with or without PEG mucus vector (i.e., in PBS). A small number of GFPNLS-positive cells were visualized on the liver surface using a stereoscope ( Fig.13 Quantitative comparison of AAV titers in the liver by qPCR showed that the use of PEG mucus carriers significantly reduced genome copies ( Fig.14 ). Therefore, it is suggested that the use of PEG mucus carrier can reduce long-range off-target effects.
[0075] Behavior of nanoparticles on the surface of skin ulcers A series of in vivo experiments showed that PEG mucus is a useful carrier for surface-specific AAV gene delivery, while PEG sponges and PEG hydrogels, on the other hand, showed reduced gene delivery efficiency themselves. This difference is believed to be related to the release profile of PEG mucus, as shown in in vitro evaluations. To elucidate the possible mechanistic properties unique to PEG mucus, the behavior of nanoparticles in the surface of skin ulcers was evaluated.
[0076] In the initial test, green fluorescent nanoparticles (about 30nm in diameter) in PBS were inoculated. The nanoparticles were initially located in the surface layer and diffused to deeper layers, such as fat or muscle tissue, over time. Importantly, very few particles remained on the ulcer surface after 24 hours. Therefore, 24 hours was used as the experimental time frame to quantitatively analyze the effect of PEG support on nanoparticle release and PEG dissolution.
[0077] Green fluorescent nanoparticles were mixed with PEG carrier or PBS and inoculated into ulcers ( Fig.15 When PEG support was used, it was found that the nanoparticles were better retained in the surface layer than those in PBS over 24 hours. In particular, the trend was more pronounced for PEG mucus or soft mucus than for PEG hydrogel or PEG sponge ( Fig.16 ). The surface-specific distribution of extended nanoparticles based on PEG mucus carriers may be related to surface-specific AAV gene delivery. The in vivo gene delivery efficiency is different depending on the type of carrier PEG. This difference is believed to be caused by the dissolution mechanism depending on the cross-linking form.
[0078] observe The PEG hydrogel and PEG sponge used as comparative examples have a structure in which all molecules are connected by irreversible bonding. Therefore, they have the characteristic properties of solids. In vitro characterization showed that they exhibited a limited elastic modulus ( Figure 4 ). In vitro evaluation of the PEG dissolution rate and particle release rate showed that both rates were significantly delayed when applied to the hydrogel and sponge. This suggests that the nanoparticles are trapped in the network ( Figure 6 ).
[0079] It is generally believed that solid polymer materials such as PEG hydrogels or sponges do not degrade gradually from the surface, but rather uniformly, which is called overall degradation. That is, due to hydrolysis, chain shearing occurs uniformly over time. Ultimately, when network connectivity is below a certain level, PEG hydrogels and sponges shift from solid to liquid. It is therefore believed that after being decomposed in PEG hydrogels and sponges, the release of AAV particles is reduced due to the penetration of AAV particles into the tissues ( Fig.17 a). Indeed, experiments with fluorescent particles used to assess the physical movement of nanoparticles showed that both the hydrogel and the sponge reduced the number of particles in the superficial ulcer layer ( Fig.17 ).
[0080] Successful endocytosis requires direct contact of AAV particles with cells. Therefore, under conditions where AAV particles are not in direct contact with cells, AAV infection is inhibited when they are trapped in the PEG network. In other words, unreleased AAV particles are not infectious. After AAV administration using PEG hydrogels or sponges, GFP expression in the ulcer surface is reduced.
[0081] On the other hand, in the PEG mucus carrier of the present invention which is in a state of equilibrium between binding and dissociation, the constituent molecules are bound by reversible bonding. The elastic modulus of the mucus gradually decreases and reaches zero over time ( Figure 4 ). This indicates that mucus is a liquid from a thermodynamic point of view. Therefore, PEG mucus applied to the ulcer surface will diffuse as a liquid and penetrate from the ulcer surface to the deeper tissue. PEG mucus and PBS are equivalent in terms of vector and AAV diffusion.
[0082] However, PEG mucus showed significant characteristics different from PBS. The dissolution rate and release rate of mucus were lower than those of PBS ( Figure 6 ), and the dissolution rate and release rate per hour are almost the same ( Figure 7 These results suggest that particle release occurs simultaneously with local dissociation of the PEG itself from the mucus. In fact, the nanoparticles contained in the PEG mucus are trapped on the ulcer surface after application ( Fig.16 ), limiting penetration from the interstitium to the deeper tissues. That is, unlike solid PEG hydrogels or sponges, particles in liquid PEG mucus diffuse in a translational manner, and AAV infection occurs mainly on the surface of ulcers where PEG mucus is present ( Fig.17 b).
[0083] In addition, during viral infection, PEG mucus is more localized than the highly viscoelastic PEG soft mucus, which results in a reduction in deep infection ( Fig.12 ). As deep infection of local off-targets is limited, expression of distant off-targets in the liver is also reduced.
Claims
1. A carrier material for local release of particulate matter, characterized in that The carrier material has a finite zero shear viscosity greater than 500 Pa·s, It contains a non-gelling polymer composed of multiple hydrophilic polymer units that are reversibly bonded. Contains solvents, The polymer unit includes a first branched polymer unit having a total of two or more boronic acid-containing groups on a side chain or a terminal and a second branched polymer unit having a total of two or more diol groups on a side chain or a terminal, The polymer concentration (c) in the support material is greater than or equal to the overlap concentration (c*) of the polymer units.
2. The carrier material according to claim 1, characterized in that The particulate matter has a diameter in the range of 10-100 nm.
3. The carrier material according to claim 1, characterized in that The particulate matter is adeno-associated virus AAV.
4. The carrier material according to claim 1, characterized in that The polymer unit has a polyethylene glycol backbone or a polyethylene backbone.
5. The carrier material according to claim 1, characterized in that The first branched polymer unit is a double-branched, triple-branched, or quadruple-branched polyethylene glycol.
6. The carrier material according to claim 1, characterized in that The second branched polymer unit is a dibranched, tribranched or tetrabranched polyethylene glycol, or a dibranched polyvinyl alcohol.
7. The carrier material according to claim 1, characterized in that The first branched polymer unit has 5×10 3 -1×10 5 Molecular weight M w .
8. The carrier material according to claim 1, characterized in that The boronic acid-containing group is an aryl boronic acid which can be substituted by a halogen atom.
9. The carrier material according to claim 1, characterized in that The diol group has an open ring structure of a sugar derivative.
10. The carrier material according to claim 1, characterized in that The third polymer unit having a total of two or more boronic acid-containing groups or diol groups at the side chain or the terminal is also included.
11. The carrier material according to claim 1, characterized in that The osmotic pressure of the carrier material is less than the osmotic pressure Π0 represented by the following formula, wherein the osmotic pressure unit is Pa, Mathematical formula 1: In the formula, c represents the polymer concentration, c* represents the overlap concentration of the polymer units, R represents the gas constant, T represents the absolute temperature, and M is the weight average molecular weight of the polymer units, wherein the unit of polymer concentration is g / L.
12. The carrier material according to claim 1, characterized in that The carrier material has the ability to release the particulate matter in vivo as the carrier material is eluted, and the elution rate L and the release rate M at this time satisfy the following relationship: Mathematical formula 2: L = A × M, In the formula, A is in the range of 0.9<A<1.
1.
13. The carrier material according to claim 1, characterized in that The use of the local release is gene therapy for skin ulcers.
14. A composition comprising the carrier material according to any one of claims 1 to 13 and the granular substance stored therein.
15. A method of treatment, comprising applying the composition of claim 14 to an affected area.
16. A kit for forming the carrier material according to any one of claims 1 to 13, characterized in that The invention comprises at least a composition A containing a first branched polymer unit having two or more boronic acid groups in a side chain or at a terminal and a composition B containing a second branched polymer unit having two or more diol groups in a side chain or at a terminal, wherein the carrier material has a finite zero shear viscosity greater than 500 Pa·s, and the polymer content (c) in the carrier material is greater than or equal to the overlap concentration (c*) of the polymer units.
17. The kit according to claim 16, characterized in that Also included is a polymer solution C containing a third polymer unit having a total of two or more boronic acid-containing groups or diol groups at a side chain or a terminal.
Citation Information
Patent Citations
Gel-forming composition for medical use, devices for the application of the composition, and drug release controlling carrier
WO2007083522A1